Application of network pharmacology in traditional Chinese medicine for the treatment of digestive system diseases - Zheng, Shihao; Liang, Yijun; Xue, Tianyu; Wang, Wei; Li, Size; Zhang, Peng; Li, Xiaoke; Cao, Xu; Liu, Qiyao; Qi, Wenying; Ye, Yongan; Zao, Xiaobin (Frontiers in Pharmacology, 2024)
With the general improvement in living standards in recent years, people’s living habits, including their dietary habits, have changed. More people around the world do not follow a healthy diet, leading to an increase in morbidity and even mortality due to digestive system diseases, which shows an increasing trend every year. The advantage of traditional Chinese medicine (TCM) in treating digestive system diseases is evident. Consequently, the mechanisms of action of single Chinese herbs and compound Chinese medicines have become the focus of research. The research method of the network pharmacology system was highly consistent with the holistic concept of TCM, and provided a new perspective and theoretical basis for basic research on digestive system diseases. This article summarizes the common databases currently used in research on TCM. It also briefly introduces the basic methods and technologies of network pharmacology studies. It also summarizes the advancements of network pharmacology technology through a comprehensive literature search on PubMed. Based on this analysis, we further explored the role of TCM in treating digestive system diseases, including chronic gastritis, gastric cancer, ulcerative colitis, and liver cirrhosis. This study provides new ideas and references for treating digestive system diseases with TCM in the future and serves as a reference for relevant researchers.